Potência aeróbia estimada de uma equipe de futsal sub-17 da região oeste do Paraná - Daniele Hoffmann; Cassiane Lui; Fernando de S. Campos; Antônio Cardoso; Robson R. Olivoto; Renan F. H. Nunes; Lucinar J. F. Flores (Universidade Estadual do Oeste do Paraná, 2016)
The study evaluate the aerobic power levels of a Futsal team sub 17 years of the West Paraná. The sample consisted of 14 male athletes of the team under 17 of Copagril team average age at 16.81±0.63. All were submitted at anthropometric tests which had variables as height, body mass and % fat. They were also carried out a pubertal questionnaire and incremental test intermittent running (HRCT) to estimate maximal aerobic power. The data were presented by descriptive analysis by calculating the mean and standard deviation. The results were height (1.74±0.07 meters), body mass (70.4±7.97 kg) and % fat (15.6±5.71). The values of HRCT test: HRmax (182.8±27.92 bpm), speed peak (PV) (13.93±1.10 km.h-1) and aerobic power (48.75±3.85 ml.kg-1.min-1). Observing the physiological values of our study with athletes under 17 Futsal, we can conclude that were found lower values than studies with professional athletes, which was expected and also presented in the literature. This implies that the athletes are still forming from the physiological point of view and they will also need to improve the level of aerobic fitness, thereby they can have a chance to be in a professional level team one day.